2020
DOI: 10.1021/acs.jafc.0c04729
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Humic Acid in Lignite Using Molybdate-Phosphorus Hierarchical Hollow Nanosphere Catalyst Oxidation: Molecular Characterization and Rice Seed Germination-Promoting Performances

Abstract: Although solid-phase activation of lignite using a nanocatalyst has great potential in producing low-cost and sustainable humic acid, the large-scale application of this technology still faces challenges because of the high price and toxicity of the nanocatalyst. Additionally, the specific molecular components of humic acid in activated lignite remain unknown. In this work, a multifunctional molybdate-phosphorus hierarchical hollow nanosphere (Mo-P-HH) catalyst was successfully manufactured by a simple way fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Thus, the experiment was arranged by an L9 (3 3 ) orthogonal table and the arrangement is shown in Table 1. The composition of the WHSs was determined by a previously developed method, 7 and nitrogen content was measured with Kjeldahl nitrogen determination apparatus (K1160, hannon, China). The static grading effect was performed by adding 0.2 g of sample and 10 mL of deionized water into a transparent glass bottle.…”
Section: Selection Of Optimal Ass Activation Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the experiment was arranged by an L9 (3 3 ) orthogonal table and the arrangement is shown in Table 1. The composition of the WHSs was determined by a previously developed method, 7 and nitrogen content was measured with Kjeldahl nitrogen determination apparatus (K1160, hannon, China). The static grading effect was performed by adding 0.2 g of sample and 10 mL of deionized water into a transparent glass bottle.…”
Section: Selection Of Optimal Ass Activation Conditionsmentioning
confidence: 99%
“…6 However, humic substance in lignite is fixed by calcium and magnesium and, thus, cannot be directly utilized by crops. Activation processes thus are often applied to convert lignite humic substance into water-soluble form for plant uptake, 7 which is also called "water-soluble humic substances" (WHSs). Traditional lignite activation method uses strong oxidants such as HNO 3 , H 2 O 2 , and KMnO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that LRC indeed reduces volatilization loss of N from urea-amended soil by inhibiting urease activity, thus increasing urea-N availability for plants [151,152]. Some studies already demonstrated that LRC can be also successfully employed in the synthesis of controlled-release fertilizers based on urea, formaldehyde, and KH 2 PO 4 [107,153]. More recently, LRC-urea granulates came into focus since they offer good predictable performance, the vast availability of the substrate, and a standardized production process [112,139].…”
Section: Sole Lrc and Hs Applicationmentioning
confidence: 99%
“…The extraction of humic acid materials, accounting for 30% to 80% of weathered coal weight (Zheng 1991;Qian et al 2015) has become an important area of research. Chemical (Fong et al 2007;Zhumanova et al 2010;Doskočil et al 2014), physical (Gazso 1997Liang et al 2011), biological (Hofrichter et al 1999;Gao et al 2012), and nanocatalyst (Tang et al 2017(Tang et al , 2020Song et al 2022) methods have been employed to activate the humic acids in the low-rank coal. Humic acid is beneficial for agricultural production because it improves soil quality (Sun et al 2020) and plant quality (Omer et al 2020;Kishor et al 2021;Çöl Keskin and Akınerdem 2021), increases fertilizer efficacy (Kishor et al 2021), stimulates plant growth (Omer et al 2020;Çöl Keskin and Akınerdem 2021;Kishor et al 2021), and enhances plant resistance to stress (Abdellatif et al 2017;Cha et al 2017;Qin and Leskovar 2020).…”
Section: Introductionmentioning
confidence: 99%